CD96 Correlates With Immune Infiltration and Impacts Patient Prognosis: A Pan-Cancer Analysis - Ye, Wenrui; Luo, Cong; Liu, Fangkun; Liu, Zhixiong; Chen, Fenghua (Frontiers in Oncology, 2021)
Background: Immunotherapy has led to significant improvements in patient outcomes, but meets hurdles recently. CD96, a novel immune checkpoint expressed on T and natural killer (NK) cells, is essential for regulating immune functions. However, the correlation of CD96 with immune infiltration and patient prognosis in pan-cancer remains unclear. Methods: HPA, TCGA, GEO, GTEx, Oncomine, TIMER2.0, PrognoScan, Linkedomics, Metascape, and GEPIA2 databases were used to analyze CD96 in cancers. Visualization of data was mostly achieved by R language, version 4.0.2. Results: In general, CD96 was differentially expressed between most cancer and adjacent normal tissues. CD96 significantly impacted the prognosis of diverse cancers. Especially, high CD96 expression was associated with poorer overall survival (OS) and disease-specific survival (DSS) in the TCGA lower grade glioma (LGG) cohort (OS, HR = 2.18, 95% CI = 1.79-2.66, P < 0.001). The opposite effect was significantly observed in skin cutaneous melanoma (SKCM) cohort (OS, HR = 0.96, 95% CI = 0.94-0.98, P < 0.001). Notably, the CD96 mutation frequency was highest in SKCM among all cancer types. Furthermore, CD96 was significantly associated with recognized immune checkpoints in most cancers, and CD96 expression was strongly correlated with multiple immune infiltrates including CD8+ T cells, dendric cells (DCs), macrophages, monocytes, NK cells, neutrophils, regulatory T cells (Tregs), and follicular helper T cells (Tfh), though subtle differences existed among some cancers. CD96 was identified as a risk factor, protective factor, and irrelevant variable in LGG, SKCM and adrenocortical carcinoma (ACC), respectively. We found CD96 related genes involved in negative regulation of leukocyte in LGG, however, involved in multiple positive immune processes in SKCM. Furthermore, elevated CD96 expression was significantly associated to the expression of various markers associated with particular immune cell subsets. Importantly, it strongly correlated with markers of T helper cell 1 (Th1) in SKCM, but not in LGG or ACC either. Conclusions: CD96 participates diverse immune responses, governs immune cell infiltration, and impacts malignant properties of various cancer types, thus standing as a potential biomarker for determining patient prognosis and immune infiltration in multiple cancers.